1988
DOI: 10.1073/pnas.85.18.6919
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins D and M mediate signals that are qualitatively different in B cells with an immature phenotype.

Abstract: The CH family of murine B-cell lymphomas includes several members that are sensitive to growth inhibition when their membrane IgM (mIgM) receptors are crosslinked by anti-p chain, anti-c chain, or anti-idiotypic antibodies. These lymphomas are IgM+, Ia+, and IgD and resemble neonatal B cells in terms of their exquisite sensitivity to anti-IgM-mediated negative signaling as a model for tolerance induction. In this report, we describe the properties of one of these lymphomas, CH33, which had been transfected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…These cells do not cease proliferation, and apoptosis does not occur (54). Similar results were obtained by Ales-Martinez and coworkers with another B-cell line, CH33, also transfected to express IgD (2). Furthermore, mutants of WEHI 231 resistant to anti-IgM-induced apoptosis display only a transient increase in c-myc RNA levels following anti-Ig treatment (29), whereas treatment of WEHI 231 cells with transforming growth factor ␤ (TGF-␤) induces a drop in levels of c-myc expression and subsequently apoptosis (56).…”
supporting
confidence: 75%
“…These cells do not cease proliferation, and apoptosis does not occur (54). Similar results were obtained by Ales-Martinez and coworkers with another B-cell line, CH33, also transfected to express IgD (2). Furthermore, mutants of WEHI 231 resistant to anti-IgM-induced apoptosis display only a transient increase in c-myc RNA levels following anti-Ig treatment (29), whereas treatment of WEHI 231 cells with transforming growth factor ␤ (TGF-␤) induces a drop in levels of c-myc expression and subsequently apoptosis (56).…”
supporting
confidence: 75%
“…Our laboratory has investigated mechanisms by which the B cell Ag receptor (BCR) 4 induces apoptosis in several B cell lines as a model for tolerance. Others and we have shown that anti-IgM (anti-heavy chain, anti-) and not anti-IgD (anti-␦ heavy chain, anti-␦) induces growth arrest and apoptosis (2)(3)(4)(5)(6). Furthermore, we have also established that anti-, but not anti-␦, stimulates an increase in expression of the cyclin-dependent kinase (CDK) inhibitor, p27 Kip1 , which is concomitant with a net loss in c-Myc protein expression (5,7,8).…”
Section: Role Of Phosphatidylinositol 3-kinase Inmentioning
confidence: 99%
“…In contrast to anti-, anti-IgD (anti-␦) treatment causes neither growth arrest nor apoptosis in the ECH408, as well as other surface IgD (sIgD) expressing lines (2,3,17,25). The results presented in Table I Kip1 protein expression in other B cell lymphoma lines (7,8,38,39).…”
Section: Anti-ig-mediated Regulation Of C-myc and P27 Kip1 Protein Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Following exposure for fluorography, individual bands were excised for phosphoamino acid analysis (26) and phosphotryptic peptide mapping (33 (1,6,44). The in vitro phosphorylation of proteins associated with membrane IgM and IgD was next compared (Fig.…”
mentioning
confidence: 99%